Character of somatic and psycho-emotional disorders in children with various types of juvenile arthritis - OV, Efimenko; MSh, Ganieva; LR, Khaidarova (Journal of Cardiovascular Medicine and Cardiology, 2023)
Rheumatic diseases in children are a source of serious medical, social, and personal problems due to the prevalence, and severity of pain syndrome, progressive course with involvement of internal organs and disorders in the psycho-emotional sphere in the pathological process. The nature of somatic and psycho-emotional disorders was studied in 70 children aged 7 years - 16 years old with various types of Juvenile Rheumatoid Arthritis (JRA). The severe course of the disease, and as a result, disability, leads to emotional instability and social maladjustment of children. The predominance of articular forms with a primary lesion of the joints of the lower extremities and their deformation was remarkable. In children with a systemic variant of JRA, kidney damage was detected in the form of urinary syndrome and tubulointerstitial nephritis. Headache was the leading clinical manifestation of autonomic disorders caused by vascular disorders.